Rubber elastic backing plate under high-strength low-rigidity iron backing plate and preparation method thereof

By using natural rubber and butyl rubber under the iron pads with elastic pads made of carbon black, white carbon black and other materials, the problem of the increase in static stiffness of the elastic pads after long-term parking in the prior art is solved, and the effect of high strength and low static stiffness is achieved, and the shock absorption performance and noise control ability of the train are improved.

CN119591948AActive Publication Date: 2025-03-11HEBEI TIEKE YICHEN NEW MATERIAL TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510135489.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-07
Publication Date
2025-03-11
Estimated Expiration
2045-02-07

AI Technical Summary

Technical Problem

The existing elastic pad under the iron pad has an increase in static stiffness after long-term parking, resulting in poor shock absorption effect of the train and unable to effectively reduce noise and vibration.

Method used

Natural rubber and butyl rubber are used as the main rubber species. The reinforcement performance is enhanced by adding large materials such as carbon black and white carbon black, while medium materials such as anti-aging agents are added to improve aging performance, and small materials such as accelerators are added to improve vulcanization efficiency. The overall coordination of the formula makes the pad have high strength and low static stiffness characteristics.

Benefits of technology

It reduces the production cost of elastic pads, and also has the advantages of high strength and low stiffness. It can maintain low static stiffness after long-term parking, ensuring the shock absorption effect and noise control of the train.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention belongs to the technical field of railway turnout fasteners, and provides a high-strength low-rigidity rubber elastic base plate under an iron base plate and a preparation method thereof. The rubber composition comprises the following raw materials in parts by weight: 65-75 parts of natural rubber, 25-35 parts of butadiene rubber, 38-46 parts of carbon black, 22-28 parts of white carbon black, 5-7 parts of zinc oxide, 2-4 parts of stearic acid, 3-5 parts of an anti-aging agent, 2-6 parts of a coupling agent, 1-3 parts of microcrystalline wax, 3-5.4 parts of an accelerant and 1-3 parts of masterbatch S-80. The coupling agent is prepared from the following components in parts by weight: 1 to 3 parts of 3-octanoylthio-1-propyltriethoxysilane and 1 to 3 parts of ethyltrimethoxysilane. By means of the method, the production cost of the elastic base plate is reduced, and meanwhile the elastic base plate has the advantages of being high in strength and low in rigidity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of railway turnout fasteners and relates to a rubber elastic pad under a high-strength and low-rigidity iron pad and a preparation method thereof. Background Art

[0002] The elastic pad under the iron pad is a key component of railway fasteners and is widely used in heavy-duty railways at home and abroad. It is used to provide track elasticity, which can buffer the high-speed impact vibration generated when vehicles pass through the rails and protect the roadbed and sleepers. The elastic pad under the iron pad is mostly made of thermoplastic polyester elastomer (TPEE) injection molding, which has excellent chemical stability and good processability. However, TPEE is expensive and tends to increase static stiffness when parked for a long time, thus failing to provide sufficient shock absorption effect for the train, failing to effectively reduce noise and vibration, and causing the train to be subjected to greater shock and vibration.

[0003] In the existing technology, in addition to thermoplastic polyester elastomer (TPEE), rubber materials, polyurethane (PU), and thermoplastic polyurethane elastomer (TPU) are also widely used; and rubber is an ideal material due to its low cost, good shock absorption effect, and good weather resistance. However, it also has some shortcomings in practical applications: the strength is not high enough, and long-term parking may also lead to increased static stiffness, affecting its shock absorption effect. Summary of the invention

[0004] The present invention provides a high-strength and low-rigidity rubber elastic pad under an iron pad and a preparation method thereof. The method provided by the present invention reduces the production cost of the elastic pad, and at the same time the elastic pad has the advantages of high strength and low rigidity.

[0005] The technical solution of the present invention is achieved in this way: A high-strength and low-rigidity rubber elastic pad under an iron pad, the raw materials comprising, by weight, 65-75 parts of natural rubber, 25-35 parts of butadiene rubber, 38-46 parts of carbon black, 22-28 parts of white carbon black, 5-7 parts of zinc oxide, 2-4 parts of stearic acid, 3-5 parts of antioxidant, 2-6 parts of coupling agent, 1-3 parts of microcrystalline wax, 3-5.4 parts of accelerator, and 1-3 parts of masterbatch S-80; the coupling agent is composed of 1-3 parts of 3-octanoylthio-1-propyltriethoxysilane and 1-3 parts of ethyltrimethoxysilane; the accelerator is selected from two or more of accelerator TMTD, accelerator NOBS, accelerator MBTS and accelerator DPTT.

[0006] Preferably, the coupling agent consists of 2 parts of 3-octanoylthio-1-propyltriethoxysilane and 2 parts of ethyltrimethoxysilane.

[0007] Preferably, the carbon black consists of 19-23 parts of carbon black N330 and 19-23 parts of carbon black N650.

[0008] Preferably, the antioxidant is selected from one or more of antioxidant AW, antioxidant 4020 and antioxidant H71.

[0009] Preferably, the antioxidant consists of 1-2 parts of antioxidant AW, 1-2 parts of antioxidant 4020 and 1-2 parts of antioxidant H71.

[0010] Preferably, the accelerator consists of 0.2-0.4 parts of accelerator TMTD, 1-3 parts of accelerator NOBS, 1-2 parts of accelerator MBTS and 0.2-0.6 parts of accelerator DPTT.

[0011] The method for preparing the rubber elastic pad under the high-strength and low-rigidity iron pad comprises the following steps: A. Prepare materials; B. Plasticate the natural rubber, leave it for 3-5 hours and then mix it with butadiene rubber; Then add white carbon black, carbon black, zinc oxide, stearic acid, microcrystalline wax, antioxidant and coupling agent for mixing, and discharge when the temperature reaches 110-120℃; C. Add the material from step B to the mixing mill. Let the rubber fall naturally on the plate once, cut it with a knife and let it fall on the plate once. Add the accelerator and masterbatch S-80. When adding, keep close to the rubber surface and add them evenly in an S shape. Finally, add all the remaining material in the basin along the roller surface. After adding, put the remaining rubber on the roller, cut it with a knife and let it fall naturally on the plate once. Adjust the roller distance to 0.4-1.6mm, then apply glue thinly, make a triangle bag, apply thinly, adjust the roller distance to apply glue, and unload the sheet. After unloading, the rubber mixture is left to stand for 24-28 hours, and then made into rubber blanks.

[0012] D. Place the rubber blank obtained in step C in a flat vulcanizer for vulcanization, and obtain a finished product after vulcanization; wherein the vulcanization temperature is 150-160° C., the vulcanization time is 10-12 min, and the vulcanization pressure is 15-17 MPa.

[0013] Preferably, in the step B, the coupling agent is first pre-emulsified, the white carbon black and the ethanol solution are blended, and ultrasonic oscillation is performed; then, when the temperature is heated to 75-85°C, the pH value is adjusted to 4-6; when the temperature is stabilized at 83-87°C, the pre-emulsified coupling agent is added dropwise, and after the addition is completed, the reaction is stirred at a rate of 200-300 rpm for 3-5 hours, and aged for 1.5-2.5 hours; then, the white carbon black powder is washed, filtered, and dried to obtain the white carbon black powder; The natural rubber is plasticized and then allowed to stand for 3-5 hours before being mixed with butadiene rubber; Then add white carbon black powder, carbon black, zinc oxide, stearic acid, microcrystalline wax and antioxidant for mixing, and discharge when the temperature reaches 110-120℃; The dosage of the white carbon black and the ethanol solution is 20-30 g:180-250 mL; the ethanol solution is an ethanol aqueous solution with a mass fraction of 90%.

[0014] Preferably, the specific conditions of the plasticizing in step B are as follows: temperature is 130-140°C, time is 240s-340s, upper push bolt pressure is 6-8 kg / cm², and rotation speed is 30-40rpm; Preferably, the specific conditions of the combined smelting are as follows: temperature is 70-80°C, time is 110-120s, and upper push bolt pressure is 6-8 kg / cm²; Preferably, the specific conditions for mixing are as follows: the rotation speed is 15-20 rpm, and the mixing time is 480s-720s.

[0015] Preferably, the specific steps of the pre-emulsification include: adding the coupling agent into deionized water, stirring at a rate of 500-1000 rpm, then dropping the emulsifier dodecylphenol polyoxyethylene ether (OP-10), the amount of the emulsifier being 5%-20% of the mass of the coupling agent, and continuing stirring for 5-10 minutes to form a stable pre-emulsion; Preferably, the specific conditions of the ultrasonic oscillation are as follows: time is 30-50 min, ultrasonic power is 180-250 W, and ultrasonic frequency is 33-40 kHz; Preferably, glacial acetic acid is used to adjust the pH value; Preferably, the washing is carried out using anhydrous ethanol; Preferably, the specific conditions for drying are as follows: placing in a vacuum drying oven at 85-95°C for 8-12 hours.

[0016] The working principle and beneficial effects of the present invention are: 1. In the present invention, rubber is used to replace TPEE, and natural rubber and butadiene rubber are used as the main rubber types. The reinforcement performance is enhanced by adding large materials such as carbon black and white carbon black, the aging performance of the elastic pad under the iron pad is improved by adding medium materials such as antioxidants, and the vulcanization efficiency is improved by adding small materials such as accelerators. The overall synergy of the formula makes the pad have the characteristics of high strength and low static stiffness.

[0017] 2. In the present invention, 3-octanoylthio-1-propyltriethoxysilane and ethyltrimethoxysilane are used to react with other components. After adding ethyltrimethoxysilane for modification, it is connected to the rubber matrix in a physically entangled manner. 3-octanoylthio-1-propyltriethoxysilane has a strong anti-scorch ability, which improves the dispersibility of white carbon black in the rubber material; when the two are used together, a part of the sulfur element in the molecular structure can break the chain to generate free sulfur, participate in vulcanization cross-linking, and a part of it participates in the hanging chain reinforcement of white carbon black to generate a single chain structure, which improves the mechanical strength of the rubber, while improving the wear resistance and compression performance of the rubber and reducing the viscosity of the rubber. Further, the present invention adopts a method of modifying white carbon black with a coupling agent. Compared with the method of direct in-situ grafting, the coupling agent can react with the surface hydroxyl group of white carbon black and interact with the rubber molecular chain, so that the white carbon black is more evenly dispersed in the rubber and the interfacial bonding force is enhanced. During the stretching process, stress can be more effectively transmitted and dispersed through white carbon black, thereby improving the tensile strength of the rubber.

[0018] 3. In the present invention, carbon black is used as a filler to improve the strength of the rubber elastic pad. Among them, commercially available carbon black grades can be used, such as carbon black N330, carbon black N650 or carbon black N330. However, if only one type of carbon black, such as carbon black N330, is used, its resistance is not large enough and does not meet the use requirements of the rubber pad under the iron pad. If carbon black N330 and carbon black N650 are used at the same time, not only the strength of the rubber elastic pad is improved, but also its resistance meets the specific use requirements of the rubber pad. DETAILED DESCRIPTION

[0019] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] The various instruments, equipment, raw materials or reagents used in the embodiments of the present invention are not particularly limited in terms of their sources, and are all conventional products that can be purchased through regular commercial channels, or can be prepared according to conventional methods well known to those skilled in the art. Among them, the chemical name of antioxidant AW is ethoxyquinoline; the chemical name of antioxidant 4020 is N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine; the chemical name of antioxidant H71 is N,N'-diphenyl-1,4-phenylenediamine; the chemical name of accelerator TMTD is tetramethylthiuram disulfide; the chemical name of accelerator NOBS is N-(oxydiethylene)-2-benzothiazolesulfonamide; the chemical name of accelerator MBTS is dibenzothiazole disulfide; and the chemical name of accelerator The chemical name of the agent DPTT is dipentylene thiuram tetrasulfide; the brand of natural rubber can be No. 1, No. 2 or No. 3 smoked sheet rubber, and the brand of natural rubber in the following embodiments and comparative examples is No. 3 smoked sheet rubber, i.e. 3# smoked sheet rubber; the brand of butadiene rubber is BR9000; the white carbon black adopts German Degussa VN3, which is a precipitated white carbon black, and the CTAB adsorption specific surface area is 138-168m² / g; the masterbatch S-80 is purchased from Nanjing Foster Technology Co., Ltd., and the effective sulfur content is ≥80%.

[0021] Example 1 A high-strength and low-rigidity rubber elastic pad under an iron pad, the raw materials comprising by weight: 75 parts of 3# smoked sheet rubber, 25 parts of butadiene rubber, 19 parts of carbon black N330, 19 parts of carbon black N650, 28 parts of white carbon black, 5 parts of zinc oxide, 4 parts of stearic acid, 1 part of antioxidant AW, 1 part of antioxidant 4020, 1 part of antioxidant H71, 4 parts of coupling agent, 3 parts of microcrystalline wax, 0.4 parts of accelerator TMTD, 1 part of accelerator NOBS, 1 part of accelerator MBTS, 0.6 parts of accelerator DPTT, and 1 part of masterbatch S-80; the coupling agent is composed of 1 part of 3-octanoylthio-1-propyltriethoxysilane and 3 parts of ethyltrimethoxysilane; The method for preparing the rubber elastic pad under the high-strength and low-rigidity iron pad comprises the following steps: A. Prepare the materials as above; B. Plasticize 3# cigarette sheet rubber at 130℃, 240s, 6kg / cm², 30rpm, and then mix with butyl rubber at 70℃, 110s, 6kg / cm²; Then add white carbon black, carbon black, zinc oxide, stearic acid, microcrystalline wax, antioxidant and coupling agent for mixing, the speed is 15 rpm, the mixing time is 480 s, and the material is discharged when the temperature reaches 110°C; C. Add the material from step B to the mixing mill. Let the rubber fall naturally on the plate once, cut it with a knife and let it fall on the plate once. Add the accelerator and masterbatch S-80. When adding, keep close to the rubber surface and add it evenly in an S shape to prevent it from lifting. Finally, add all the remaining material in the basin along the roller surface. After adding, put the remaining rubber on the roller, cut it with a knife and let it fall naturally on the plate once. Adjust the roller distance to 0.4mm, then apply glue thinly once, make a triangle bag, apply thinly once, adjust the roller distance to apply glue, and unload the sheet. After unloading, the mixed rubber is left to stand for 24 hours, and the mixed rubber is made into rubber blanks; D. Place the rubber blank obtained in step C in a flat vulcanizer for vulcanization, and obtain a finished product after vulcanization; the vulcanization temperature is 150° C., the vulcanization time is 10 min, and the vulcanization pressure is 15 MPa.

[0022] Example 2 A high-strength and low-rigidity rubber elastic pad under an iron pad, the raw materials comprising by weight: 70 parts of 3# smoked sheet rubber, 30 parts of butadiene rubber, 21 parts of carbon black N330, 21 parts of carbon black N650, 25 parts of white carbon black, 6 parts of zinc oxide, 3 parts of stearic acid, 1 part of antioxidant AW, 2 parts of antioxidant 4020, 1 part of antioxidant H71, 4 parts of coupling agent, 2 parts of microcrystalline wax, 0.3 parts of accelerator TMTD, 2 parts of accelerator NOBS, 1.5 parts of accelerator MBTS, 0.4 parts of accelerator DPTT, and 2 parts of masterbatch S-80; the coupling agent is composed of 2 parts of 3-octanoylthio-1-propyltriethoxysilane and 2 parts of ethyltrimethoxysilane; The method for preparing the rubber elastic pad under the high-strength and low-rigidity iron pad comprises the following steps: A. Prepare the materials as above; B. Plasticize 3# cigarette sheet rubber at 135℃, 290s, 7kg / cm², 35rpm, and then mix with butyl rubber at 75℃, 115s, 7kg / cm². Then add white carbon black, carbon black, zinc oxide, stearic acid, microcrystalline wax, antioxidant and coupling agent for mixing, the speed is 18rpm, the mixing time is 600s, and the material is discharged when the temperature reaches 115℃; C. Add the material from step B to the mixing mill. Let the rubber fall naturally on the plate once, cut it with a knife and let it fall on the plate once. Add the accelerator and masterbatch S-80. When adding, keep close to the rubber surface and add it evenly in an S shape to prevent it from lifting. Finally, add all the remaining material in the basin along the roller surface. After adding, put the remaining rubber on the roller, cut it with a knife and let it fall naturally on the plate once. Adjust the roller distance to 1mm, then apply glue thinly once, make a triangle bag, apply thinly once, adjust the roller distance to apply glue, and unload the sheet. After unloading, the mixed rubber is left to stand for 24 hours, and the mixed rubber is made into rubber blanks; D. Place the rubber blank obtained in step C in a flat vulcanizer for vulcanization, and obtain a finished product after vulcanization; the vulcanization temperature is 155° C., the vulcanization time is 11 min, and the vulcanization pressure is 16 MPa.

[0023] Example 3 A high-strength and low-rigidity rubber elastic pad under an iron pad, the raw materials comprising by weight: 65 parts of 3# smoked sheet rubber, 35 parts of butadiene rubber, 23 parts of carbon black N330, 23 parts of carbon black N650, 22 parts of white carbon black, 7 parts of zinc oxide, 2 parts of stearic acid, 2 parts of antioxidant AW, 2 parts of antioxidant 4020, 1 part of antioxidant H71, 4 parts of coupling agent, 1 part of microcrystalline wax, 0.2 parts of accelerator TMTD, 3 parts of accelerator NOBS, 2 parts of accelerator MBTS, 0.2 parts of accelerator DPTT, and 3 parts of masterbatch S-80; the coupling agent is composed of 3 parts of 3-octanoylthio-1-propyltriethoxysilane and 1 part of ethyltrimethoxysilane; The method for preparing the rubber elastic pad under the high-strength and low-rigidity iron pad comprises the following steps: A. Prepare the materials as above; B. Plasticize 3# cigarette sheet rubber at 140℃, 340s, 8kg / cm² pressure, 40rpm speed, and then mix with butyl rubber at 80℃, 120s, 8kg / cm² pressure after 5 hours of storage. Then add white carbon black, carbon black, zinc oxide, stearic acid, microcrystalline wax, antioxidant and coupling agent for mixing, the speed is 20rpm, the mixing time is 720s, and the material is discharged when the temperature reaches 120℃; C. Add the material from step B to the mixing mill. Let the rubber fall naturally on the plate once, cut it with a knife and let it fall on the plate once. Add the accelerator and masterbatch S-80. When adding, keep close to the rubber surface and add it evenly in an S shape to prevent it from lifting. Finally, add all the remaining material in the basin along the roller surface. After adding, put the remaining rubber on the roller, cut it with a knife and let it fall naturally on the plate once. Adjust the roller distance to 1.6mm, then apply glue thinly once, make a triangle bag, apply thinly once, adjust the roller distance to apply glue, and unload the sheet. After unloading, the mixed rubber is left to stand for 28 hours, and the mixed rubber is made into rubber blanks; D. Place the rubber blank obtained in step C in a flat vulcanizer for vulcanization, and obtain a finished product after vulcanization; the vulcanization temperature is 160° C., the vulcanization time is 12 min, and the vulcanization pressure is 17 MPa.

[0024] Example 4 A high-strength and low-rigidity rubber elastic pad under an iron pad, the raw materials comprising by weight: 70 parts of 3# smoked sheet rubber, 30 parts of butadiene rubber, 20 parts of carbon black N330, 26 parts of white carbon black, 20 parts of carbon black N650, 6 parts of zinc oxide, 3 parts of stearic acid, 4 parts of antioxidant 4020, 2 parts of coupling agent, 2 parts of microcrystalline wax, 0.3 parts of accelerator TMTD, 2 parts of accelerator NOBS, 1.5 parts of accelerator MBTS, 0.4 parts of accelerator DPTT, and 2 parts of masterbatch S-80; the coupling agent is composed of 1 part of 3-octanoylthio-1-propyltriethoxysilane and 1 part of ethyltrimethoxysilane; The method for preparing the rubber elastic pad under the high-strength and low-rigidity iron pad comprises the following steps: A. Prepare the materials as above; B. Plasticize 3# cigarette sheet rubber at 135℃, 290s, 7kg / cm², 35rpm, and then mix with butyl rubber at 75℃, 115s, 7kg / cm². Then add white carbon black, carbon black, zinc oxide, stearic acid, microcrystalline wax, antioxidant and coupling agent for mixing, the speed is 18rpm, the mixing time is 600s, and the material is discharged when the temperature reaches 115℃; C. Add the material from step B to the mixing mill. Let the rubber fall naturally on the plate once, cut it with a knife and let it fall on the plate once. Add the accelerator and masterbatch S-80. When adding, keep close to the rubber surface and add it evenly in an S shape to prevent it from lifting. Finally, add all the remaining material in the basin along the roller surface. After adding, put the remaining rubber on the roller, cut it with a knife and let it fall naturally on the plate once. Adjust the roller distance to 1mm, then apply glue thinly once, make a triangle bag, apply thinly once, adjust the roller distance to apply glue, and unload the sheet. After unloading, the mixed rubber is left to stand for 24 hours, and the mixed rubber is made into rubber blanks; D. Place the rubber blank obtained in step C in a flat vulcanizer for vulcanization, and obtain a finished product after vulcanization; the vulcanization temperature is 155° C., the vulcanization time is 11 min, and the vulcanization pressure is 16 MPa.

[0025] Example 5 A high-strength and low-rigidity rubber elastic pad under an iron pad, the raw materials comprising by weight: 70 parts of 3# tobacco sheet rubber, 30 parts of butadiene rubber, 42 parts of carbon black N650, 23 parts of white carbon black, 6 parts of zinc oxide, 3 parts of stearic acid, 1 part of antioxidant AW, 1 part of antioxidant 4020, 2 parts of antioxidant H71, 6 parts of coupling agent, 2 parts of microcrystalline wax, 2 parts of accelerator TMTD, 2 parts of accelerator NOBS, and 2 parts of masterbatch S-80; the coupling agent is composed of 3 parts of 3-octanoylthio-1-propyltriethoxysilane and 3 parts of ethyltrimethoxysilane; The method for preparing the rubber elastic pad under the high-strength and low-rigidity iron pad comprises the following steps: A. Prepare the materials as above; B. Plasticize 3# cigarette sheet rubber at 135℃, 290s, 7kg / cm², 35rpm, and then mix with butyl rubber at 75℃, 115s, 7kg / cm². Then add white carbon black, carbon black, zinc oxide, stearic acid, microcrystalline wax, antioxidant and coupling agent for mixing, the speed is 18rpm, the mixing time is 600s, and the material is discharged when the temperature reaches 115℃; C. Add the material from step B to the mixing mill. Let the rubber fall naturally on the plate once, cut it with a knife and let it fall on the plate once. Add the accelerator and masterbatch S-80. When adding, keep close to the rubber surface and add it evenly in an S shape to prevent it from lifting. Finally, add all the remaining material in the basin along the roller surface. After adding, put the remaining rubber on the roller, cut it with a knife and let it fall naturally on the plate once. Adjust the roller distance to 1mm, then apply glue thinly once, make a triangle bag, apply thinly once, adjust the roller distance to apply glue, and unload the sheet. After unloading, the mixed rubber is left to stand for 24 hours, and the mixed rubber is made into rubber blanks; D. Place the rubber blank obtained in step C in a flat vulcanizer for vulcanization, and obtain a finished product after vulcanization; the vulcanization temperature is 155° C., the vulcanization time is 11 min, and the vulcanization pressure is 16 MPa.

[0026] Example 6 A high-strength and low-rigidity rubber elastic pad under an iron pad, the raw materials comprising by weight: 70 parts of 3# smoked sheet rubber, 30 parts of butadiene rubber, 21 parts of carbon black N330, 21 parts of carbon black N650, 25 parts of white carbon black, 6 parts of zinc oxide, 3 parts of stearic acid, 1 part of antioxidant AW, 2 parts of antioxidant 4020, 1 part of antioxidant H71, 4 parts of coupling agent, 2 parts of microcrystalline wax, 0.3 parts of accelerator TMTD, 2 parts of accelerator NOBS, 1.5 parts of accelerator MBTS, 0.4 parts of accelerator DPTT, and 2 parts of masterbatch S-80; the coupling agent is composed of 2 parts of 3-octanoylthio-1-propyltriethoxysilane and 2 parts of ethyltrimethoxysilane; The method for preparing the rubber elastic pad under the high-strength and low-rigidity iron pad comprises the following steps: A. Prepare the materials as above; B. First, the coupling agent is pre-emulsified, and the white carbon black is mixed with a 90% ethanol aqueous solution by mass, and ultrasonically oscillated; then, when the temperature is heated to 80°C, the pH value is adjusted to 5; when the temperature is stabilized at 85°C, the pre-emulsified coupling agent is added dropwise, and after the addition is completed, reflux condensation is performed during the reaction process, and the reaction is stirred at a rate of 250 rpm for 4 hours and aged for 2 hours; then, the white carbon black powder is washed, filtered, and dried to obtain the white carbon black powder; The 3# cigarette sheet rubber was plasticized at a temperature of 135°C, a time of 290 seconds, a top bolt pressure of 7 kg / cm², and a rotation speed of 35 rpm. After standing for 4 hours, it was combined with butadiene rubber at a temperature of 75°C, a time of 115 seconds, and a top bolt pressure of 7 kg / cm². Then add white carbon black powder, carbon black, zinc oxide, stearic acid, microcrystalline wax and antioxidant for mixing at a speed of 18 rpm for 600 s, and discharge when the temperature reaches 115°C; The amount of white carbon black and ethanol aqueous solution is 25g:220mL; The specific steps of the pre-emulsification include: adding a coupling agent into deionized water, stirring at a rate of 800 rpm, then dropping an emulsifier of dodecylphenol polyoxyethylene ether, the amount of the emulsifier being 10% of the mass of the coupling agent, and continuing stirring for 8 minutes to form a stable pre-emulsion; The ultrasonic oscillation is performed for 40 minutes, the ultrasonic power is 200W, and the ultrasonic frequency is 35kHz; glacial acetic acid is used to adjust the pH value; anhydrous ethanol is used for washing; and the drying specifically includes: drying in a vacuum drying oven at 90°C for 10 hours; C. Add the material from step B to the mixing mill. Let the rubber fall naturally on the plate once, cut it with a knife and let it fall on the plate once. Add the accelerator and masterbatch S-80. When adding, keep close to the rubber surface and add it evenly in an S shape to prevent it from lifting. Finally, add all the remaining material in the basin along the roller surface. After adding, put the remaining rubber on the roller, cut it with a knife and let it fall naturally on the plate once. Adjust the roller distance to 1mm, then apply glue thinly once, make a triangle bag, apply thinly once, adjust the roller distance to apply glue, and unload the sheet. After unloading, the mixed rubber is left to stand for 24 hours, and the mixed rubber is made into rubber blanks; D. Place the rubber blank obtained in step C in a flat vulcanizer for vulcanization, and obtain a finished product after vulcanization; the vulcanization temperature is 155° C., the vulcanization time is 11 min, and the vulcanization pressure is 16 MPa.

[0027] Example 7 A high-strength and low-rigidity rubber elastic pad under an iron pad, the raw materials comprising by weight: 70 parts of 3# smoked sheet rubber, 30 parts of butadiene rubber, 21 parts of carbon black N330, 21 parts of carbon black N650, 25 parts of white carbon black, 6 parts of zinc oxide, 3 parts of stearic acid, 1 part of antioxidant AW, 2 parts of antioxidant 4020, 1 part of antioxidant H71, 4 parts of coupling agent, 2 parts of microcrystalline wax, 0.3 parts of accelerator TMTD, 2 parts of accelerator NOBS, 1.5 parts of accelerator MBTS, 0.4 parts of accelerator DPTT, and 2 parts of masterbatch S-80; the coupling agent is composed of 2 parts of 3-octanoylthio-1-propyltriethoxysilane and 2 parts of ethyltrimethoxysilane; The method for preparing the rubber elastic pad under the high-strength and low-rigidity iron pad comprises the following steps: A. Prepare the materials as above; B. First, the coupling agent is pre-emulsified, and the white carbon black is mixed with a 90% ethanol aqueous solution by mass, and ultrasonically oscillated; then, when the temperature is heated to 75°C, the pH value is adjusted to 6; when the temperature is stabilized at 83°C, the pre-emulsified coupling agent is added dropwise, and after the addition is completed, reflux condensation is performed during the reaction process, and stirring is performed at a rate of 200 rpm for 3 hours, and aging is performed for 1.5 hours; then, washing, suction filtration, and drying are performed to obtain white carbon black powder; The 3# cigarette sheet rubber was plasticized at a temperature of 135°C, a time of 290 seconds, a top bolt pressure of 7 kg / cm², and a rotation speed of 35 rpm. After standing for 4 hours, it was combined with butadiene rubber at a temperature of 75°C, a time of 115 seconds, and a top bolt pressure of 7 kg / cm². Then add white carbon black powder, carbon black, zinc oxide, stearic acid, microcrystalline wax and antioxidant for mixing at a speed of 18 rpm for 600 s, and discharge when the temperature reaches 115°C; The amount of white carbon black and ethanol aqueous solution is 20g:180mL; The specific steps of the pre-emulsification include: adding a coupling agent into deionized water, stirring at a rate of 500 rpm, then dropping an emulsifier of dodecylphenol polyoxyethylene ether, the amount of the emulsifier being 20% ​​of the mass of the coupling agent, and continuing stirring for 5 minutes to form a stable pre-emulsion; The ultrasonic oscillation is performed for 30 minutes, the ultrasonic power is 180W, and the ultrasonic frequency is 33kHz; glacial acetic acid is used to adjust the pH value; anhydrous ethanol is used for washing; and the drying specifically includes: drying in a vacuum drying oven at 85°C for 12 hours; C. Add the material from step B to the mixing mill. Let the rubber fall naturally on the plate once, cut it with a knife and let it fall on the plate once. Add the accelerator and masterbatch S-80. When adding, keep close to the rubber surface and add it evenly in an S shape to prevent it from lifting. Finally, add all the remaining material in the basin along the roller surface. After adding, put the remaining rubber on the roller, cut it with a knife and let it fall naturally on the plate once. Adjust the roller distance to 1mm, then apply glue thinly once, make a triangle bag, apply thinly once, adjust the roller distance to apply glue, and unload the sheet. After unloading, the mixed rubber is left to stand for 24 hours, and the mixed rubber is made into rubber blanks; D. Place the rubber blank obtained in step C in a flat vulcanizer for vulcanization, and obtain a finished product after vulcanization; the vulcanization temperature is 155° C., the vulcanization time is 11 min, and the vulcanization pressure is 16 MPa.

[0028] Example 8 A high-strength and low-rigidity rubber elastic pad under an iron pad, the raw materials comprising by weight: 70 parts of 3# smoked sheet rubber, 30 parts of butadiene rubber, 21 parts of carbon black N330, 21 parts of carbon black N650, 25 parts of white carbon black, 6 parts of zinc oxide, 3 parts of stearic acid, 1 part of antioxidant AW, 2 parts of antioxidant 4020, 1 part of antioxidant H71, 4 parts of coupling agent, 2 parts of microcrystalline wax, 0.3 parts of accelerator TMTD, 2 parts of accelerator NOBS, 1.5 parts of accelerator MBTS, 0.4 parts of accelerator DPTT, and 2 parts of masterbatch S-80; the coupling agent is composed of 2 parts of 3-octanoylthio-1-propyltriethoxysilane and 2 parts of ethyltrimethoxysilane; The method for preparing the rubber elastic pad under the high-strength and low-rigidity iron pad comprises the following steps: A. Prepare the materials as above; B. First, the coupling agent is pre-emulsified, and the white carbon black is mixed with a 90% ethanol aqueous solution by mass, and ultrasonically oscillated; then, when the temperature is heated to 85°C, the pH value is adjusted to 4; when the temperature is stabilized at 87°C, the pre-emulsified coupling agent is added dropwise, and after the addition is completed, reflux condensation is performed during the reaction process, and stirring is performed at a rate of 300 rpm for 5 hours, and aging is performed for 2.5 hours; then, washing, filtering, and drying are performed to obtain white carbon black powder; The 3# cigarette sheet rubber was plasticized at a temperature of 135°C, a time of 290 seconds, a top bolt pressure of 7 kg / cm², and a rotation speed of 35 rpm. After standing for 4 hours, it was combined with butadiene rubber at a temperature of 75°C, a time of 115 seconds, and a top bolt pressure of 7 kg / cm². Then add white carbon black powder, carbon black, zinc oxide, stearic acid, microcrystalline wax and antioxidant for mixing at a speed of 18 rpm for 600 s, and discharge when the temperature reaches 115°C; The amount of white carbon black and ethanol aqueous solution is 30g:250mL; The specific steps of the pre-emulsification include: adding a coupling agent into deionized water, stirring at a rate of 1000 rpm, then dropping an emulsifier of dodecylphenol polyoxyethylene ether, the amount of the emulsifier being 5% of the mass of the coupling agent, and continuing stirring for 10 minutes to form a stable pre-emulsion; The ultrasonic oscillation is performed for 50 minutes, the ultrasonic power is 250W, and the ultrasonic frequency is 40kHz; glacial acetic acid is used to adjust the pH value; anhydrous ethanol is used for washing; and the drying specifically includes: drying in a vacuum drying oven at 95°C for 12 hours; C. Add the material from step B to the mixing mill. Let the rubber fall naturally on the plate once, cut it with a knife and let it fall on the plate once. Add the accelerator and masterbatch S-80. When adding, keep close to the rubber surface and add it evenly in an S shape to prevent it from lifting. Finally, add all the remaining material in the basin along the roller surface. After adding, put the remaining rubber on the roller, cut it with a knife and let it fall naturally on the plate once. Adjust the roller distance to 1mm, then apply glue thinly once, make a triangle bag, apply thinly once, adjust the roller distance to apply glue, and unload the sheet. After unloading, the mixed rubber is left to stand for 24 hours, and the mixed rubber is made into rubber blanks; D. Place the rubber blank obtained in step C in a flat vulcanizer for vulcanization, and obtain a finished product after vulcanization; the vulcanization temperature is 155° C., the vulcanization time is 11 min, and the vulcanization pressure is 16 MPa.

[0029] Comparative Example 1 A rubber elastic pad, comprising, by weight, 70 parts of 3# smoked sheet rubber, 30 parts of butadiene rubber, 21 parts of carbon black N330, 21 parts of carbon black N650, 25 parts of white carbon black, 6 parts of zinc oxide, 3 parts of stearic acid, 1 part of antioxidant AW, 2 parts of antioxidant 4020, 1 part of antioxidant H71, 4 parts of coupling agent, 2 parts of microcrystalline wax, 0.3 parts of accelerator TMTD, 2 parts of accelerator NOBS, 1.5 parts of accelerator MBTS, 0.4 parts of accelerator DPTT, and 2 parts of masterbatch S-80; the coupling agent is 3-octanoylthio-1-propyltriethoxysilane; The method for preparing the rubber elastic pad under the high-strength and low-rigidity iron pad comprises the following steps: A. Prepare the materials as above; B. Plasticize 3# cigarette sheet rubber at 135℃, 290s, 7kg / cm², 35rpm, and then mix with butyl rubber at 75℃, 115s, 7kg / cm². Then add white carbon black, carbon black, zinc oxide, stearic acid, microcrystalline wax, antioxidant and coupling agent for mixing, the speed is 18rpm, the mixing time is 600s, and the material is discharged when the temperature reaches 115℃; C. Add the material from step B to the mixing mill. Let the rubber fall naturally on the plate once, cut it with a knife and let it fall on the plate once. Add the accelerator and masterbatch S-80. When adding, keep close to the rubber surface and add it evenly in an S shape to prevent it from lifting. Finally, add all the remaining material in the basin along the roller surface. After adding, put the remaining rubber on the roller, cut it with a knife and let it fall naturally on the plate once. Adjust the roller distance to 1mm, then apply glue thinly once, make a triangle bag, apply thinly once, adjust the roller distance to apply glue, and unload the sheet. After unloading, the mixed rubber is left to stand for 24 hours, and the mixed rubber is made into rubber blanks; D. Place the rubber blank obtained in step C in a flat vulcanizer for vulcanization, and obtain a finished product after vulcanization; the vulcanization temperature is 155° C., the vulcanization time is 11 min, and the vulcanization pressure is 16 MPa.

[0030] Comparative Example 2 A rubber elastic pad, the raw materials comprising by weight: 70 parts of 3# smoked sheet rubber, 30 parts of butadiene rubber, 21 parts of carbon black N330, 21 parts of carbon black N650, 25 parts of white carbon black, 6 parts of zinc oxide, 3 parts of stearic acid, 1 part of antioxidant AW, 2 parts of antioxidant 4020, 1 part of antioxidant H71, 4 parts of coupling agent, 2 parts of microcrystalline wax, 0.3 parts of accelerator TMTD, 2 parts of accelerator NOBS, 1.5 parts of accelerator MBTS, 0.4 parts of accelerator DPTT, 2 parts of masterbatch S-80; the coupling agent is ethyltrimethoxysilane; The method for preparing the rubber elastic pad under the high-strength and low-rigidity iron pad comprises the following steps: A. Prepare the materials as above; B. Plasticize 3# cigarette sheet rubber at 135℃, 290s, 7kg / cm², 35rpm, and then mix with butyl rubber at 75℃, 115s, 7kg / cm². Then add white carbon black, carbon black, zinc oxide, stearic acid, microcrystalline wax, antioxidant and coupling agent for mixing, the speed is 18rpm, the mixing time is 600s, and the material is discharged when the temperature reaches 115℃; C. Add the material from step B to the mixing mill. Let the rubber fall naturally on the plate once, cut it with a knife and let it fall on the plate once. Add the accelerator and masterbatch S-80. When adding, keep close to the rubber surface and add it evenly in an S shape to prevent it from lifting. Finally, add all the remaining material in the basin along the roller surface. After adding, put the remaining rubber on the roller, cut it with a knife and let it fall naturally on the plate once. Adjust the roller distance to 1mm, then apply glue thinly once, make a triangle bag, apply thinly once, adjust the roller distance to apply glue, and unload the sheet. After unloading, the mixed rubber is left to stand for 24 hours, and the mixed rubber is made into rubber blanks; D. Place the rubber blank obtained in step C in a flat vulcanizer for vulcanization, and obtain a finished product after vulcanization; the vulcanization temperature is 155° C., the vulcanization time is 11 min, and the vulcanization pressure is 16 MPa.

[0031] Comparative Example 3 A rubber elastic pad, the raw materials comprising by weight: 70 parts of 3# smoked sheet rubber, 30 parts of butadiene rubber, 21 parts of carbon black N330, 21 parts of carbon black N650, 25 parts of white carbon black, 6 parts of zinc oxide, 3 parts of stearic acid, 1 part of antioxidant AW, 2 parts of antioxidant 4020, 1 part of antioxidant H71, 2 parts of microcrystalline wax, 0.3 parts of accelerator TMTD, 2 parts of accelerator NOBS, 1.5 parts of accelerator MBTS, 0.4 parts of accelerator DPTT, 2 parts of masterbatch S-80; The method for preparing the rubber elastic pad under the high-strength and low-rigidity iron pad comprises the following steps: A. Prepare the materials as above; B. Plasticize 3# cigarette sheet rubber at 135℃, 290s, 7kg / cm², 35rpm, and then mix with butyl rubber at 75℃, 115s, 7kg / cm². Then add white carbon black, carbon black, zinc oxide, stearic acid, microcrystalline wax and antioxidant for mixing at a speed of 18 rpm for 600 s, and discharge when the temperature reaches 115°C; C. Add the material from step B to the mixing mill. Let the rubber fall naturally on the plate once, cut it with a knife and let it fall on the plate once. Add the accelerator and masterbatch S-80. When adding, keep close to the rubber surface and add it evenly in an S shape to prevent it from lifting. Finally, add all the remaining material in the basin along the roller surface. After adding, put the remaining rubber on the roller, cut it with a knife and let it fall naturally on the plate once. Adjust the roller distance to 1mm, then apply glue thinly once, make a triangle bag, apply thinly once, adjust the roller distance to apply glue, and unload the sheet. After unloading, the mixed rubber is left to stand for 24 hours, and the mixed rubber is made into rubber blanks; D. Place the rubber blank obtained in step C in a flat vulcanizer for vulcanization, and obtain a finished product after vulcanization; the vulcanization temperature is 155° C., the vulcanization time is 11 min, and the vulcanization pressure is 16 MPa.

[0032] Comparative Example 4 A rubber elastic pad, comprising, by weight, 70 parts of 3# smoked sheet rubber, 30 parts of butadiene rubber, 21 parts of carbon black N330, 21 parts of carbon black N650, 25 parts of white carbon black, 6 parts of zinc oxide, 3 parts of stearic acid, 1 part of antioxidant AW, 2 parts of antioxidant 4020, 1 part of antioxidant H71, 4 parts of coupling agent, 2 parts of microcrystalline wax, 0.3 parts of accelerator TMTD, 2 parts of accelerator NOBS, 1.5 parts of accelerator MBTS, 0.4 parts of accelerator DPTT, and 2 parts of masterbatch S-80; the coupling agent is composed of 2 parts of 3-octanoylthio-1-propyltriethoxysilane and 2 parts of 3-mercaptopropyltrimethoxysilane; The method for preparing the rubber elastic pad under the high-strength and low-rigidity iron pad comprises the following steps: A. Prepare the materials as above; B. Plasticize 3# cigarette sheet rubber at 135℃, 290s, 7kg / cm², 35rpm, and then mix with butyl rubber at 75℃, 115s, 7kg / cm². Then add white carbon black, carbon black, zinc oxide, stearic acid, microcrystalline wax, antioxidant and coupling agent for mixing, the speed is 18rpm, the mixing time is 600s, and the material is discharged when the temperature reaches 115℃; C. Add the material from step B to the mixing mill. Let the rubber fall naturally on the plate once, cut it with a knife and let it fall on the plate once. Add the accelerator and masterbatch S-80. When adding, keep close to the rubber surface and add it evenly in an S shape to prevent it from lifting. Finally, add all the remaining material in the basin along the roller surface. After adding, put the remaining rubber on the roller, cut it with a knife and let it fall naturally on the plate once. Adjust the roller distance to 1mm, then apply glue thinly once, make a triangle bag, apply thinly once, adjust the roller distance to apply glue, and unload the sheet. After unloading, the mixed rubber is left to stand for 24 hours, and the mixed rubber is made into rubber blanks; D. Place the rubber blank obtained in step C in a flat vulcanizer for vulcanization, and obtain a finished product after vulcanization; the vulcanization temperature is 155° C., the vulcanization time is 11 min, and the vulcanization pressure is 16 MPa.

[0033] Performance Testing In order to better illustrate the characteristics of the pad provided by the embodiment of the present invention, the products prepared in the comparative example and the embodiment were tested for corresponding performances according to TB / T 3395.4, and the results are shown in Table 1-2.

[0034] Table 1

[0035] Table 2

[0036] The rubber pads prepared in Examples 1-8 of the present invention can maintain a static stiffness below 47 mm / kN after long-term storage (3 months). It can be seen that the overall synergy of the formulation of the present invention enables the pads to have the characteristics of high strength and low static stiffness.

[0037] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A high-strength and low-rigidity rubber elastic pad under an iron pad, characterized in that: The raw materials include, by weight: 65-75 parts of natural rubber, 25-35 parts of butadiene rubber, 38-46 parts of carbon black, 22-28 parts of white carbon black, 5-7 parts of zinc oxide, 2-4 parts of stearic acid, 3-5 parts of antioxidant, 2-6 parts of coupling agent, 1-3 parts of microcrystalline wax, 3-5.4 parts of accelerator, 1-3 parts of masterbatch S-80; the coupling agent is composed of 1-3 parts of 3-octanoylthio-1-propyltriethoxysilane and 1-3 parts of ethyltrimethoxysilane; the accelerator is selected from two or more of accelerator TMTD, accelerator NOBS, accelerator MBTS and accelerator DPTT.

2. The high-strength and low-rigidity rubber elastic pad under the iron pad according to claim 1, characterized in that: The coupling agent is composed of 2 parts of 3-octanoylthio-1-propyltriethoxysilane and 2 parts of ethyltrimethoxysilane.

3. The high-strength and low-rigidity rubber elastic pad under the iron pad according to claim 1, characterized in that: The carbon black consists of 19-23 parts of carbon black N330 and 19-23 parts of carbon black N650.

4. The high-strength and low-rigidity rubber elastic pad under the iron pad according to claim 1, characterized in that: The antioxidant is selected from one or more of antioxidant AW, antioxidant 4020 and antioxidant H71.

5. The high-strength and low-rigidity rubber elastic pad under the iron pad according to claim 1, characterized in that: The antioxidant consists of 1-2 parts of antioxidant AW, 1-2 parts of antioxidant 4020 and 1-2 parts of antioxidant H71.

6. The high-strength and low-rigidity rubber elastic pad under the iron pad according to claim 1, characterized in that: The accelerator is composed of 0.2-0.4 parts of accelerator TMTD, 1-3 parts of accelerator NOBS, 1-2 parts of accelerator MBTS and 0.2-0.6 parts of accelerator DPTT.

7. The method for preparing the rubber elastic pad under the high-strength and low-rigidity iron pad according to any one of claims 1 to 6, characterized in that: The following steps are involved: A. Prepare materials; B. Plasticate the natural rubber, leave it for 3-5 hours and then mix it with butadiene rubber; Then add white carbon black, carbon black, zinc oxide, stearic acid, microcrystalline wax, antioxidant and coupling agent for mixing, and discharge when the temperature reaches 110-120℃; C. Add the material from step B to the mixing mill. Let the rubber fall naturally on the plate once, cut it with a knife and let it fall on the plate once. Add the accelerator and masterbatch S-80. When adding, keep close to the rubber surface and add them evenly in an S shape. Finally, add all the remaining material in the basin along the roller surface. After adding, put the remaining rubber on the roller, cut it with a knife and let it fall naturally on the plate once. Adjust the roller distance to 0.4-1.6mm, then apply glue thinly, make a triangle bag, apply thinly, adjust the roller distance to apply glue, and unload the sheet. After unloading, the mixed rubber is left to stand for 24-28 hours, and the mixed rubber is made into rubber blanks; D. Place the rubber blank obtained in step C in a flat vulcanizer for vulcanization, and obtain a finished product after vulcanization; wherein the vulcanization temperature is 150-160° C., the vulcanization time is 10-12 min, and the vulcanization pressure is 15-17 MPa.

8. The method for preparing the rubber elastic pad under the high-strength and low-rigidity iron pad according to claim 7, characterized in that: In the step B, the coupling agent is first pre-emulsified, and the white carbon black and the ethanol solution are mixed and ultrasonically oscillated; then the temperature is heated to 75-85°C, and the pH value is adjusted to 4-6; when the temperature is stabilized at 83-87°C, the pre-emulsified coupling agent is added dropwise, and after the addition is completed, the reaction is stirred at a rate of 200-300 rpm for 3-5 hours, and aged for 1.5-2.5 hours; then washed, filtered, and dried to obtain white carbon black powder; The natural rubber is plasticized and then allowed to stand for 3-5 hours before being mixed with butadiene rubber; Then add white carbon black powder, carbon black, zinc oxide, stearic acid, microcrystalline wax and antioxidant for mixing, and discharge when the temperature reaches 110-120℃; The dosage of the white carbon black and the ethanol solution is 20-30 g:180-250 mL; the ethanol solution is an ethanol aqueous solution with a mass fraction of 90%.

9. The method for preparing the rubber elastic pad under the high-strength and low-rigidity iron pad according to claim 7, characterized in that: The specific conditions of the plasticating in step B are as follows: temperature of 130-140°C, time of 240s-340s, upper push bolt pressure of 6-8 kg / cm², and rotation speed of 30-40rpm; The specific conditions of smelting are as follows: temperature is 70-80℃, time is 110-120s, upper bolt pressure is 6-8 kg / cm²; The specific conditions of mixing are as follows: the rotation speed is 15-20 rpm, and the mixing time is 480s-720s.

10. The method for preparing the rubber elastic pad under the high-strength and low-rigidity iron pad according to claim 8, characterized in that: The specific steps of the pre-emulsification include: adding the coupling agent into deionized water, stirring at a rate of 500-1000 rpm, then dropping an emulsifier, the amount of the emulsifier being 5%-20% of the mass of the coupling agent, and continuing to stir for 5-10 minutes to form a stable pre-emulsion; The specific conditions of the ultrasonic oscillation are as follows: time is 30-50min, ultrasonic power is 180-250W, and ultrasonic frequency is 33-40kHz; glacial acetic acid is used for adjusting the pH value; anhydrous ethanol is used for washing; the specific conditions of the drying are as follows: put it into a vacuum drying oven at 85-95°C and dry it for 8-12h.

Citation Information

Patent Citations

  • Rubber backing plate of passenger dedicated line

    CN101381485A

  • Creep-resisting and aging-resisting rubber tie plate under rail and preparation method thereof

    CN101659762A

  • High-abrasion resistance reinforcing material for tires and preparation method of high-abrasion resistance reinforcing material

    CN104356444A

  • Rubber filler, preparation method thereof and rubber material

    CN116239821A

  • Rubber, preparation method thereof and sleeper mat

    CN118459903A